2013
DOI: 10.1016/j.rboe.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Simvastatin in the Process of Fracture Healing in Tibiae of Rats

Abstract: Objective Evaluate the effects of simvastatin in the process of fracture healing in rat tibia. Methods Thirty-six rats were subjected to diaphyseal fracture of the leg bones and divided in the statin group (GE) and control group (GC), being subdivided into three subgroups according to days post-fracture (7th, 14th and 28th day) to assess bone healing. In GE was administered by gavage a solution of simvastatin to the sacrifice. In the control group was administered salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…SIM can induce a significant cell death in a wide range of human tumor cell lines including glioblastoma, astrocytoma, neuroblastoma, lung adenocarcinoma, and breast cancer via decreasing mevalonate formation and downstream farnesyl pyrophosphate (FPP) [39]. FPP inhibits epithelialization and wound healing through the glucocorticoid receptor and its reduction can enhance the epithelialization [40]. SIM also showed anabolic effect on bone with stimulation of bone tissue formation, Oxlund and Andreessen found that treatment with SIM at a dose of 20 mg/kg orally partially impeded bone loss in female Wistar rats that were subjected to ovariectomy, and also increased cortical bone formation.…”
Section: Simvastatin (Sim)mentioning
confidence: 99%
“…SIM can induce a significant cell death in a wide range of human tumor cell lines including glioblastoma, astrocytoma, neuroblastoma, lung adenocarcinoma, and breast cancer via decreasing mevalonate formation and downstream farnesyl pyrophosphate (FPP) [39]. FPP inhibits epithelialization and wound healing through the glucocorticoid receptor and its reduction can enhance the epithelialization [40]. SIM also showed anabolic effect on bone with stimulation of bone tissue formation, Oxlund and Andreessen found that treatment with SIM at a dose of 20 mg/kg orally partially impeded bone loss in female Wistar rats that were subjected to ovariectomy, and also increased cortical bone formation.…”
Section: Simvastatin (Sim)mentioning
confidence: 99%
“…This scale involves scoring fibrous tissue, cartilage tissue, immature and mature bone ratios within the healing area formed on the proximal and distal sides of the fracture line as indicators of healing. In other studies, the assessment scale described by Vasconcelos et al 26 was adopted. This scale employs a 0-4 scoring system to indicate the stage of the healing tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are a group of lipid-lowering drugs widely used to prevent cardiovascular events; they act on cholesterol-lowering activity and have pleiotropic effects, including bone stimulation, promotion of vasculogenesis and immunomodulation of anti-inflammatory effects [14]. Several studies have indicated that statins act on bone remodeling and the formation of bone tissue, being an osteoinductive substance [15].…”
Section: Introductionmentioning
confidence: 99%
“…Statins act by inhibiting the mevalonate pathway, a precursor for the formation of steroids and steroid isoprenoids; they also inhibit the activity of 3-hydroxy-3-methylglutarylcoenzyme A reductase (HMG-CoA), reducing the synthesis of cholesterol, which is required for the conversion of HMG-CoA to mevalonate. Thus, by acting to reduce the synthesis of mevalonate, they interfere with the proliferation and activities of cells [15]. One study demonstrated that statins stimulate bone formation associated with increased expression of the BMP-2 gene in bone cells and that they act as markers in enhanced gene expression for vascular endothelial growth factor (VEGF) [19].…”
Section: Introductionmentioning
confidence: 99%